Optimization of fuel production from waste vehicle tires by pyrolysis and resembling to diesel fuel by various desulfurization methods - Aydin, Huseyin; Ilkilic, Cumali (Elsevier Sci Ltd, 2012)
In this study, an alternative fuel for diesel engines was produced from waste automobile tires by the method of pyrolysis. In order to reduce the high sulfur content of the fuel, CaO, Ca(OH)(2), and NaOH catalysts were used. In addition, effects of variables such as temperature, the catalyst ratio and the N-2 flow rate on yield were investigated. The highest product yield was obtained with temperature of 500 degrees C and 200 cm(3)/min N-2 flow rate. When compared with the products obtained from initial pyrolysis, the sulfur content of the product was found to be 34.25% lower with the utilization of 5% Ca(OH)(2) in the reaction. In order to make the sulfur content of the product closer diesel fuel, the acetic acid-H2O2, formic acid-H2O2 and H2SO4 were used in different proportions. Although, the other acids were also very effective, the use of 10% H2SO4 reduced sulfur content of the product by 75.27%. Thus, with 5% Ca(OH)(2) and then with addition of 10% H2SO4, the sulfur content of the product was reduced by 83.75%. The properties of diesel fuel (DF), liquid fuel derived from waste vehicle tires (TF), low sulfur tire fuel (LSTF) and fuel mixtures of LSTF-DF were analyzed. It was found that, the density and sulfur content of LSTF fuel were slightly higher than that of diesel fuel, but other features and distillation curves were very close to diesel fuel. (C) 2012 Published by Elsevier Ltd.
Keywords: Vehicle tires; Pyrolysis; Acidic desulfurization; Diesel fuel